'It's like the gold rush': the lives and careers of professional video game streamers on Twitch.tv. Issue 3 (23rd February 2019) - Johnson, Mark R.; Woodcock, Jamie
ABSTRACT: This paper explores the lives and careers of video game live broadcasters, especially those who gain their primary real-world income through this practice. We introduce the dominant market leader – the platform Twitch.tv – and outline its immensely rapid growth and the communities of millions of broadcasters, and tens of millions of viewers, it now boasts. Drawing on original interview data with professional and aspiring-professional game broadcasters ('streamers'), we examine the pasts, presents, and anticipated futures of streamers: how professional streamers began streaming, the everyday labour practices of streaming, and their concerns and hopes about the future of their chosen career. Through these examinations we explore the sociotechnical entanglements – digital intimacy, celebrity, content creation, and video games – that exemplify this new media form. Live streaming is an online practice expanding in both production and consumption at immense speed, and Twitch and its streamers appear to be at the forefront of that revolution.